Yeast-model-based study identified myosin- and calcium-dependent calmodulin signalling as a potential target for drug intervention in chorea-acanthocytosis - Piotr Soczewka; Damian Kolakowski; Iwona Smaczynska-de Rooij; Weronika Rzepnikowska; Kathryn R. Ayscough; Joanna Kaminska; Teresa Zoladek (The Company of Biologists, 2019)
Chorea-acanthocytosis (ChAc) is a rare neurodegenerative disease associated with mutations in the human VPS13A gene. The mechanism of ChAc pathogenesis is unclear. A simple yeast model was used to investigate the function of the single yeast VSP13 orthologue, Vps13. Vps13, like human VPS13A, is involved in vesicular protein transport, actin cytoskeleton organisation and phospholipid metabolism. A newly identified phenotype of the vps13Δ mutant, sodium dodecyl sulphate (SDS) hypersensitivity, was used to screen a yeast genomic library for multicopy suppressors. A fragment of the MYO3 gene, encoding Myo3-N (the N-terminal part of myosin, a protein involved in the actin cytoskeleton and in endocytosis), was isolated. Myo3-N protein contains a motor head domain and a linker. The linker contains IQ motifs that mediate the binding of calmodulin, a negative regulator of myosin function. Amino acid substitutions that disrupt the interaction of Myo3-N with calmodulin resulted in the loss of vps13Δ suppression. Production of Myo3-N downregulated the activity of calcineurin, a protein phosphatase regulated by calmodulin, and alleviated some defects in early endocytosis events. Importantly, ethylene glycol tetraacetic acid (EGTA), which sequesters calcium and thus downregulates calmodulin and calcineurin, was a potent suppressor of vps13Δ. We propose that Myo3-N acts by sequestering calmodulin, downregulating calcineurin and increasing activity of Myo3, which is involved in endocytosis and, together with Osh2/3 proteins, functions in endoplasmic reticulum-plasma membrane contact sites. These results show that defects associated with vps13Δ could be overcome, and point to a functional connection between Vps13 and calcium signalling as a possible target for chemical intervention in ChAc. Yeast ChAc models may uncover the underlying pathological mechanisms, and may also serve as a platform for drug testing. This article has an associated First Person interview with the first author of the paper.